Eksistensi PKK (Partiya Karkeren Kurdistan) Sebagai Gerakan Separatisme di Turki - Titik Yulianingsih; Dian Sumela Utami; Muhammad Irvan Dini; Khofifah Niarni; Jati Pamungkas Al-Kausar (FISIP Universitas Tanjungpura, 2022)
This article aims to discuss how to analyze the existence of the PKK as a separatist movement in Turkey. The Turkish government and the Kurdish tribe have changed the relationship of a different past, the 20th past under the rule of Sultan Abdul Hamid. Many of the rights that were previously obtained by ethnic Kurds can no longer be obtained. Especially since Mustafa Kemal Ataturklaim was chairman of the Supreme National Assembly. Therefore, to continue to fight for their rights, the Kurdish ethnic group formed the Partiya Karkeren Kurdistan (PKK) organization on November 27, 1978, led by Abdullah Ocalan. However, it is this PKK which makes military attacks where and causes casualties, so the UN declares that the PKK is an international terrorist organization. The problem formulation will be answered using rational choice theory and using the resolution of the concept of separatism. This article is divided into four parts, namely the dynamics of PKK terrorism, the motivation and recording of recruitment of PKK members, the PKK separatism prevention movement, and the existence of PKK in Turkiye.